Delirium at the end of life. Issue 3 (June 2021) - Knoepfel, Silvana; Bode, Leonie; Gehrke, Samuel; Spiller, Tobias; Fuchs, Simon; Ernst, Jutta; von Känel, Roland; Boettger, Soenke
Abstract: Background: The general in-hospital mortality and interrelationship with delirium are vastly understudied. Therefore, this study aimed to assess the rates of in-hospital mortality and terminal delirium. Method: In this prospective cohort study of 28, 860 patients from 37 services including 718 in-hospital deaths, mortality rates and prevalence of terminal delirium were determined with simple logistic regressions and their respective odds ratios (ORs). Results: Although overall in-hospital mortality was low (2.5%), substantial variance between services became apparent: Across intensive care services the rate was 10.8% with a 5.8-fold increased risk, across medical services rates were 4.4% and 2.4-fold, whereas at the opposite end, across surgical services rates were 0.7% and 87% reduction, respectively. The highest in-hospital mortality rate occurred on the palliative care services (27.3%, OR 19.45). The general prevalence of terminal delirium was 90.7% and ranged from 83.2% to 100%. Only across intensive care services (98.1%, OR 7.48), specifically medical intensive care (98.1%, OR 7.48) and regular medical services (95.8%, OR 4.12) rates of terminal delirium were increased. In contrast, across medical services (86.4%, OR 0.32) and in particular oncology (73.9%, OR 0.25), pulmonology (72%, OR 0.31) and cardiology (63.2%, OR 0.4) rates were decreased. For the remaining services, rates of terminal delirium were the same. Significance of results: Although in-hospital mortality was low, the interrelationship with delirium was vast: most patients were delirious at the end of life. The implications of terminal delirium merit further studies.